Enhancement of molecular orientation with two super-Gaussian pulses. (6th April 2020) - Wu, Shuai-Shuai; Chai, Shuo; Ni, Shuang; Yu, Jie; Cong, Shu-Lin
Abstract: A theoretical scheme is presented to realize effective molecular orientation driven by two super-Gaussian pulses (SGPs). As an applied example, the orientation dynamics of LiH molecule is studied by using the time-dependent quantum wave packet method. The calculations are performed including both the molecular vibrational and rotational degrees of freedom. It is shown that the efficient molecular orientation can be achieved by two SGPs, and the maximal orientation degree is 0.823, which is obviously better than those by the Gaussian pulse and a single SGP. The orientation degree and orientation duration time are dependent on the laser frequency, field intensity and delay time between two SGPs. The pulse shaped parameter N characterizing the SGP has effects on molecular orientation and rotational population. Furthermore, the molecular orientation degree and orientation duration time decrease with the increase of temperature. A long-lived molecular orientation duration time and high orientation degree can be achieved in the range of temperature from 0 to 100 K.